2018
DOI: 10.31219/osf.io/zqr69
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Promoting Open Science to Increase the Trustworthiness of Evidence in Special Education

Abstract: Scientific evidence should guide the selection of practice for individuals with disabilities. Scientific evidence, however, must be trustworthy to move special education toward greater empirical certainty and more effective policies and practices. Transparency, openness, and reproducibility increase the trustworthiness of evidence. We propose that researchers in special education adopt emerging open science reforms such as preprints, data and materials sharing, preregistration of studies and analysis plans, an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…To restore this status quo, psychological science would thus need to achieve high levels of replicability. Indeed, many new methodological standards in psychology aim at increasing replicability (Cook, Lloyd, Mellor, Nosek, & Therrien, 2018; Van Bavel et al, 2016). If those standards succeed, the status quo belief that psychology is a highly replicable science might be restored.…”
Section: How Can Public Trust Be Repaired?mentioning
confidence: 99%
“…To restore this status quo, psychological science would thus need to achieve high levels of replicability. Indeed, many new methodological standards in psychology aim at increasing replicability (Cook, Lloyd, Mellor, Nosek, & Therrien, 2018; Van Bavel et al, 2016). If those standards succeed, the status quo belief that psychology is a highly replicable science might be restored.…”
Section: How Can Public Trust Be Repaired?mentioning
confidence: 99%
“…If we want special education to become a truly scientific field of study (Kauffman, 2011;, then this must apply to all research on disproportionality and all those who do or read the research as well. Cook, Lloyd, Mellor, Nosek, and Therrien (2018) have suggested that open science can increase the trustworthiness of evidence in special education. We suggest that open science be used in addressing the serious matter of disproportionality as well as the science of instruction in special education.…”
Section: Needed Researchmentioning
confidence: 99%
“…Several initiatives, often falling under the umbrella term of open science (https://cos.io/), have been developed across many scientific fields in reaction to the aforementioned challenges. Recently, several research teams have argued that education (van der Zee & Reich, 2018), special education (Adelson et al, 2019; Cook et al, 2018), and gifted education research (McBee et al, 2018) could benefit from greater adoption of open science practices such as preregistration, data and materials sharing, preprints, badges, and registered reports. 1 Vazire (2018) dubbed such actions as a credibility revolution in psychological research.…”
Section: Closing the Gap Between Research Aspiration And Research Actionmentioning
confidence: 99%